REFORMASI BIROKRASI PELAYANAN PEMBUATAN SERTIFIKAT TANAH DI KABUPATEN SIAK - Muhammad Kurnia Ramadhan; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Bureaucratic problems that occur can be seen from the still many complaints and complaints from the public directly or through the mass media to related agencies, such as complicated procedural problems, there is no certainty of the timeframe for completion, the attitude of officers who are less responsive, discriminatory in providing services, and other problems. Bureaucratic reform carried out by the government has a goal in improving the quality of public services so that the public can feel satisfaction with the services provided. This study aims to determine the quality of service bureaucracy in making land certificates in Siak Regency, both the Tangible (Direct Evidence), Reliability, Responsiveness and Assurance aspects. Then analyze the inhibiting factors in the service of making land certificates in Siak Regency which include organizational structure, policies, facilities and infrastructure as well as the mindset of employees.The results of this study are that the implementation of bureaucratic reform in making land certificate services in Siak Regency has not been optimal because the indicators that measure the quality of the bureaucracy have not been fulfilled and there are still many shortcomings that must be improved so that bureaucratic reform in the Siak Regency National Land Agency can be implemented well. It also requires the cooperation of all parties to improve the governance system to achieve the desired bureaucratic reform Keywords: Bureaucracy Reform, Public Service